Rational use of thyroid function test - Al-Ankoodi, Dr. Yasser (International Journal of Scientific Research and Management (IJSRM), 2019)
Thyroid function test (TFT) is one of the frequently asked investigations. There is continuous increase and demand for this test. The reasons for increased number of thyroid testing include the wide list of clinical presentation of thyroid disorders with variable signs and symptoms.  The thyroid gland itself can be affected with different ranges of disorders including auto-antibodies, congenital, genetics and cancers (1,2). In addition, the thyroid disorders can mimic or co-exist with other conditions especially in elderly and children.  This climbing number of tests makes a financial burden to the laboratory. It necessitated extra reagents and consumables, extra manpower and some time extra analyzer.